Pengaruh Mengajar Yang Bervariasi Terhadap Prestasi Belajar Siswa di SMP ELPIDA Kelas VII - Yanto Tefa; Yublina Tefa; Prihadi Kristiyan; Elisabeth Dethan (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2021)
This study is based on the fact that the need for competent teachers in the learning process is very necessary, because the main problem in this study is how much influence varies teaching on student learning achievement in ELPIDA Junior High School (Class VII) and how effective the implementation of varied teaching is on student learning achievement in ELPIDA Junior High School (Class VII). The method used in this study is Quantitative research with a classroom research strategy. Based on the results of the research conducted, it shows that with this student achievement, teachers can find out